2018
DOI: 10.1093/cercor/bhy084
|View full text |Cite
|
Sign up to set email alerts
|

The Low-Threshold Calcium Channel Cav3.2 Mediates Burst Firing of Mature Dentate Granule Cells

Abstract: Mature granule cells are poorly excitable neurons that were recently shown to fire action potentials, preferentially in bursts. It is believed that the particularly pronounced short-term facilitation of mossy fiber synapses makes granule cell bursting a very effective means of properly transferring information to CA3. However, the mechanism underlying the unique bursting behavior of mature granule cells is currently unknown. Here, we show that Cav3.2 T-type channels at the axon initial segment are responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 73 publications
4
28
0
Order By: Relevance
“…The main electrophysiological difference observed between DLPFC and PPC L3PNs was a higher proportion of bursting L3PNs in DLPFC. Burst firing depends on voltage-gated Ca 2ϩ channels (Williams and Stuart, 1999;Clarkson et al, 2017;Dumenieu et al, 2018) of the T-type Ca V 3 family (Nanou and Catterall, 2018). Therefore, our finding that expression of the Ca V 3 alpha 1G subunit gene CACNA1G was enriched in DLPFC L3PN samples is consistent with the larger proportion of B-L3PNs in DLPFC.…”
Section: Gene Expression Profiles Of L3pns In Dlpfc and Ppcsupporting
confidence: 75%
See 2 more Smart Citations
“…The main electrophysiological difference observed between DLPFC and PPC L3PNs was a higher proportion of bursting L3PNs in DLPFC. Burst firing depends on voltage-gated Ca 2ϩ channels (Williams and Stuart, 1999;Clarkson et al, 2017;Dumenieu et al, 2018) of the T-type Ca V 3 family (Nanou and Catterall, 2018). Therefore, our finding that expression of the Ca V 3 alpha 1G subunit gene CACNA1G was enriched in DLPFC L3PN samples is consistent with the larger proportion of B-L3PNs in DLPFC.…”
Section: Gene Expression Profiles Of L3pns In Dlpfc and Ppcsupporting
confidence: 75%
“…Interestingly, among genes identified as differentially expressed in our microarray analysis is CACNA1G (1.9-fold higher in DLPFC L3PNs). CACNA1G encodes a subunit of the T-type voltage-gated calcium channel fam-ily Ca V 3, involved in the generation of AP bursts in PNs (Williams and Stuart, 1999;Clarkson et al, 2017;Dumenieu et al, 2018). Consistent with the well-known body of data from rodent cortex showing that burst-firing PNs are widely distributed across cortical regions, CACNA1G is expressed in multiple regions of the monkey neocortex (Bernard et al, 2012).…”
Section: Dlpfc and Ppc L3pns Differ In Gene Expression Profilessupporting
confidence: 52%
See 1 more Smart Citation
“…Emerging evidence, however, suggests that both T‐type and R‐type voltage‐gated calcium channels are expressed in the AIS of several types of neurons where they may increase the probability of single spikes or contribute to burst firing (Bender & Trussell, ; Dumenieu et al . ). Recent studies also showed that axonal ion channels are targets for neuromodulation.…”
Section: Resultsmentioning
confidence: 97%
“…Doublet spiking is followed by an AHP which silences electrical activity in motoneurons, and this might facilitate force generation 70 . In mature granule neurons of the dentate gyrus, Cav3.2 supports action potential pairing within tenth of ms, while T-type channel antagonists or Cav3.2 genetic ablation lengthen this interval to no more than 75 ms 71 . In the cerebellum, long term depression at the parallel fiber – Purkinje neuron excitatory synapse is better induced by a fast pairing of parallel fiber stimulation (interval 60 ms) 72 .…”
Section: Discussionmentioning
confidence: 99%